Colonic dysmotility associated with high‐fat diet‐induced obesity: Role of enteric glia. Issue 4 (21st February 2020) - Antonioli, Luca; D'Antongiovanni, Vanessa; Pellegrini, Carolina; Fornai, Matteo; Benvenuti, Laura; di Carlo, Alma; van den Wijngaard, Renè; Caputi, Valentina; Cerantola, Silvia; Giron, Maria Cecilia; Németh, Zoltán H.; Haskó, György; et al.
Abstract: The present study was designed to examine the role of enteric glial cells (EGCs) in colonic neuromuscular dysfunctions in a mouse model of high‐fat diet (HFD)‐induced obesity. C57BL/6J mice were fed with HFD or standard diet (SD) for 1, 2, or 8 weeks. Colonic interleukin (IL)‐1β, IL‐6, and malondialdehyde (MDA) levels were measured. Expression of occludin in colonic tissues was examined by western blot. Substance P (SP), S100β, GFAP, and phosphorylated mitogen‐activated protein kinase 1 (pERK) were assessed in whole mount specimens of colonic plexus by immunohistochemistry. Colonic tachykininergic contractions, elicited by electrical stimulation or exogenous SP, were recorded in the presence or absence of fluorocitrate (FC). To mimic exposure to HFD, cultured EGCs were incubated with palmitate (PA) and/or lipopolysaccharide (LPS). SP and IL‐1β levels were assayed in the culture medium by ELISA. HFD mice displayed an increase in colonic IL‐1β and MDA, and a reduction of occludin at week 2. These changes occurred to a greater extent at week 8. In vitro electrically evoked tachykininergic contractions were enhanced in HFD mice after 2 or 8 weeks, and they were blunted by FC. Colonic IL‐6 levels as well as substance P and S100β density in myenteric ganglia of HFD mice were increased at week 8, but not at week 1 or 2. In cultured EGCs, co‐incubation with palmitate plus LPS led to a significant increase in both SP and IL‐1β release. HFD‐induced obesity is characterized by a hyperactivation of EGCs and is involved in the development of enteric motor disorders through an increase in tachykininergic activity and release of pro‐inflammatory mediators.